Prevalence of postpartum depression in Ghana: a systematic review study - Keku, Emmanuel; Asabea, Sandra; Nti, Seth Junior; Kwamekyi, Abigail (Scientific Electronic Archives, 2023)
Postpartum depression affects many women and remains the fourth-leading cause of disability and premature death. This study reviewed Ghanaian mothers’ postpartum depression studies. This systematic study examined PubMed, Scopus, Up-to-date, Science Direct, Google Scholar, and Proquest to estimate postpartum depression prevalence. Between 2009 and 2022, published papers on the prevalence of postpartum depression in English were analyzed. Postpartum depression, risk variables, and prevalence were all included in the search approach. An examination of the literature revealed that a trend in the prevalence of PPD has been identified. According to the research, Community-based research in Northern Ghana found prevalence rates between 16.8 and 33.5 percent, whereas estimates from the rest of the nation were between 3.8 and 11.3 percent. The findings from this study might also be utilized to guide future investigations and the design of preventive measures.